Interplay between structural parameters and reactivity of Zr6-based MOFs as artificial proteases. Issue 26 (29th May 2020) - Loosen, Alexandra; de Azambuja, Francisco; Smolders, Simon; Moons, Jens; Simms, Charlotte; De Vos, Dirk; Parac-Vogt, Tatjana N.
Abstract : Peptide bond hydrolysis catalyzed by NU-1000 MOF revealed key structural features that influence the catalytic performance of Zr6 based MOFs. Abstract : Structural parameters influencing the reactivity of metal–organic frameworks (MOF) are challenging to establish. However, understanding their effect is crucial to further develop their catalytic potential. Here, we uncovered a correlation between reaction kinetics and the morphological structure of MOF-nanozymes using the hydrolysis of a dipeptide under physiological pH as model reaction. Comparison of the activation parameters in the presence of NU-1000 with those observed with MOF-808 revealed the reaction outcome is largely governed by the Zr6 cluster. Additionally, its structural environment completely changes the energy profile of the hydrolysis step, resulting in a higher energy barrier Δ G ‡ for NU-1000 due to a much larger Δ S ‡ term. The reactivity of NU-1000 towards a hen egg white lysozyme protein under physiological pH was also evaluated, and the results pointed to a selective cleavage at only 3 peptide bonds. This showcases the potential of Zr-MOFs to be developed into heterogeneous catalysts for non-enzymatic but selective transformation of biomolecules, which are crucial for many modern applications in biotechnology and proteomics.